PROFICIENT DECOLORIZATION OF METHYLENE BLUE BY RETURNABLE BACILLUS COAGULANS IMMOBILIZED BEADS: KINETICS, ISOTHERMS AND THERMODYNAMIC STUDIES - PALRAJ RANGANATHAN,; V. KASIVISWANATHAN,; R. SAYEE KANNAN, (International Journal of Pharma and Bio Sciences, 2016)
The decolorization equilibria and kinetics of a cationic dye (methylene blue) were examined in this study using sodium alginate (polymer), agriculture waste stuff such as saw dust (individual and consortium) immobilized Bacillus coagulans beads as the adsorbent. Factors affecting the variety of adsorption processes: concentrations of dye (50-90 ppm), time, pH (7.0), inoculums size, temperature were investigated. The effective dye decolorization was attained within 25 hrs and MB dye removal was 98%. Captivatingly, MB dye decolorization performance of bacteria immobilized sodium alginate and saw dust beads was same that of free bacteria. We have also tested the reusability of bacteria immobilized sodium alginate (SA) and saw dust (SD) beads. The decolorization process followed by the pseudo-first-order kinetic and the Langmuir isotherm models. The determination of the thermodynamic parameters (ΔG, ΔH and ΔS) indicates the spontaneous and exothermic nature of the adsorption process. Overall, batch study indicated that this environmentally friendly adsorbent may be an alternative for the removal of methylene blue dye from contaminated media.